Factors related to Adherence to Limiting Fluid Intake in Hemodialysis Patients with Chronic Kidney Disease in Hemodialysis Room - Kartini, Yanis; Setiyawan, Roni; Astuti, Puji; Wijayanti, Lono; Soleha, Umdatus (International Journal of Psychosocial Rehabilitation, 2020)
Adherence to limiting fluid intake for hemodialysis patients is very important because fluid accumulation and cardiovascular complications might happen if they ignore it. This study was aimed at identifying the factors that relate to adherence to limiting fluid intake in the patients with chronic kidney disease in hemodialysis room of RSI Jemursari Surabaya. It is an analytic study done by using cross sectional approach. The population involved all patients with chronic kidney disease found in hemodialysis room of RSI Jemursari Surabaya, totaling 50 people in which 44 respondents were chosen as the samples by using simple random sampling technique. The independent variables comprised age, sex, level of education, level of knowledge, occupation, and family support, whereas the dependent variable was adherence in limiting fluid intake. The data were collected using questionnaire. The data were analyzed using logistic regression test (α = 0.05). The results showed that there was no correlation between age, sex, occupation and adherence (p > α (0.05); there was a correlation between knowledge and adherence (p = 0.002); there was a correlation between education and adherence (p = 0.000); and there was a correlation between family support and adherence (p = 0.000) < α (0.05). Moreover, the multiple logistic regression test showed that the factors closely related to patients’ adherence in limiting fluid intake were family support and knowledge in which they interact to one another. The higher the level of education, knowledge, and family support is, the more adherent the patients to limiting fluid intake will be. Therefore, the nurses are expected to give health education to the patients and their family to develop their knowledge and support to limit fluid intake.